2003
DOI: 10.1002/icd.284
|View full text |Cite
|
Sign up to set email alerts
|

The influence of infant irritability on maternal sensitivity in a sample of very premature infants

Abstract: Published paper ABSTRACTThe relationship between maternal sensitivity and infant irritability was investigated in a short-term longitudinal study of 29 very preterm infants. Infant irritability was assessed at term with the Brazelton NBAS, the Mother and Baby Scales (MABS) and the Crying Pattern Questionnaire (CPQ). Maternal sensitivity was assessed by nurses' ratings in the neonatal care unit and at three months during motherinfant interaction observation. Cross-lagged panel analysis indicated that neonatal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…There is reason to suspect that LBW infants may prove particularly susceptible to developmental experiences and environmental exposures. Perhaps most notably, they often show increased negative emotionality (Meier, Wolke, Gutbrod, & Rust, ) and such negativity early in life, including when prenatally ‘programmed’, has been found to operate as a plasticity factor (Pluess & Belsky, ), making children more susceptible ‘for better and for worse’. Thus, while it is well established that LBW slightly increases the risk of adverse outcomes, it may also make children more susceptible to positive environmental inputs.…”
Section: Introductionmentioning
confidence: 99%
“…There is reason to suspect that LBW infants may prove particularly susceptible to developmental experiences and environmental exposures. Perhaps most notably, they often show increased negative emotionality (Meier, Wolke, Gutbrod, & Rust, ) and such negativity early in life, including when prenatally ‘programmed’, has been found to operate as a plasticity factor (Pluess & Belsky, ), making children more susceptible ‘for better and for worse’. Thus, while it is well established that LBW slightly increases the risk of adverse outcomes, it may also make children more susceptible to positive environmental inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Vale la pena preguntarse: ¿tendrá la sensibilidad materna relación con la irritabilidad del bebé prematuro en la interacción madre-bebé? Meier, Wolke, Gutbrod & Rust (2003) estudiaron la relación entre irritabilidad y sensibilidad materna en 29 niños prematuros y sus madres. Ellos definieron como "sensiblidad" a la capacidad materna para reconocer, interpretar y responder apropiadamente a la comunicación y a las necesidades del bebé.…”
Section: Generalidades En La Interacción Madre-bebé-prematurounclassified
“…In general, more frequent positive emotion expression in children is linked with greater parent sensitivity (Braungart-Rieker, Garwood, Powers, & Wang, 2001; Miller, McDonough, Rosenblum, & Sameroff, 2002) and more frequent negative emotion expression with less sensitivity (Braungart-Rieker et al, 2001; Feldman, Dollberg, & Nadam, 2011; Miller et al, 2002; Mills-Koonce et al, 2007; Nozadi et al, 2013; Owens, Shaw & Vondra, 1998; Scaramella et al, 2008). Yet, other studies find that observed negative emotion expression is unrelated to parent sensitivity (Meier et al, 2003; Mills-Koonce et al, 2007; Pauli-Pott et al, 2000), or that more negative emotion expression is associated with greater parental responsiveness (Crockenberg & Smith, 1982). …”
Section: Introductionmentioning
confidence: 97%
“…during free play vs. frustrating task) or for certain parenting behaviors but not others (Calkins et al, 2004; Ciciolla, Crnic & West, 2013; Mills-Koonce et al, 2007). Lastly, a few studies find negative affectivity is with more sensitive parenting (Meier, Wolke, Gutbrod & Rust, 2003; Washington, Minde, & Goldberg, 1986; Zahr, 1991). …”
Section: Introductionmentioning
confidence: 99%